Restricted freedoms of menstruating women: a capability approach to period poverty - Viljoen, Hanrié (The Stellenbosch Socratic Journal, 2024)
Period poverty can generally be defined as a lack of access to or an inability to acquire, access, and perform menstrual health products, facilities, and practices. It is estimated that around 500 million women worldwide live in period poverty. This is a phenomenon which can incapacitate women from performing basic functions and from participating fully in society. In this paper, I will use the Capability Approach developed by Martha Nussbaum and Amartya Sen to show conclusively that period poverty poses a real restriction to the freedoms of menstruating women and girls. Under the Capability Approach, well-being is measured by the real ability of an individual to have certain capabilities. Specifically, period poverty restricts freedoms by having an adverse effect on education, health, and social functioning. While many of these women and girls have the formal abilities or rights to the restricted spheres, period poverty acts as a hidden barrier to successfully acquiring the capabilities of being educated, being healthy, and being social.